Autologous Breast Reconstruction With a Delay Procedure of the Deep Inferior Epigastric Artery Perforator Flap Because of Venous Congestion of the Flap on Pedicle: A Case Series. Issue 5 (May 2019) - Hillberg, Nadine S.; van Mulken, Tom J. M.; Meesters-Caberg, Marleen A. J.; Piatkowski, Andrzej; Keuter, Xavier A. H.; Hommes, Juliette; van der Hulst, René R. W.
Abstract : Abstract: The deep inferior epigastric artery perforator (DIEP) flap is one of the most used free flaps for the reconstruction of the breast after a mastectomy. Despite careful selection of the patients and preoperative imaging, difficulties in vascularization of the flap can occur in some cases. Although multiple vascular connections (bipedicled, turbocharged, or stacked) can be made in selected cases, there can still be venous congestion before the flap is transferred. Between 2016 and 2018, 4 cases in our series of 281 patients experienced such problems. Three of 4 patients had undergone preoperative imaging of the perforators by a magnetic resonance angiography or computed tomography angiography, in which a good perforator was seen. All 4 patients had a venous problem of blood circulation in the flap intraoperatively. The flaps were left to rest to decide on its venous status. Without improvement after this period of 20 to 30 minutes, the surgeons decided to withhold the translocation of the flap to the chest wall and sutured the flap back into the donor side. The final anastomosis of the DIEP flap occurred on average 8 days after the prefabrication. The translocation of the DIEP flap to the chest in this second operation went uncomplicated in all cases. Postoperatively, all patients had adequate arterial inflow and venous outflow of the flap. There were no postoperative complications. In case a DIEP flap shows venous problems before translocation, a delay procedure can be applied. In this way, the vascularization of the flap can be improved, and the translocation of the DIEP flap in a second operation can be successfully performed.